Quality of life assessment in core outcome sets: A position statement of the EADV Task Force on Quality of Life and Patient Oriented Outcomes. (23rd October 2021) - Chernyshov, P.V.; Evers, A.W.M.; Bewley, A.; Tomas‐Aragones, L.; Marron, S.E.; Manolache, L.; Pustišek, N.; Abeni, D.; Sampogna, F.; Linder, M.D.; Salek, M.S.; Szepietowski, J.C.
Abstract: Core outcome sets (COSs) are an agreed standardized collection of outcomes that should be measured and reported in all clinical trials for a specific clinical condition. Tsekhe aim of our position paper by the European Academy of Dermatology and Venereology (EADV) Task Force on Quality of Life and Patient Oriented Outcomes was to identify the challenges and Patient Oriented Outcomes advantages in the development of COSs within dermatological QoL research. Twelve EADV Task Force multidisciplinary team members presented a total of 101 items (51 advantages and 50 disadvantages). All participants considered that COS are beneficial for comparison between different studies, treatments, dermatological diseases, geographical location and ethnicities. In conclusion, the EADV Task Force on Quality of Life and Patient Oriented Outcomes has recognized the primacy of advantages of COS and deliberated that the disadvantages in COS are related to development process and use of COS.